Employability in engineering programs (LACCEI, 2024)
In the current labor context, employability is a tool that is important for graduates who enter the labor sector today and have to face a number of challenges. Where it stands out, a decline in job opportunities, rapidly changing technology, and lifelong learning. The literature explains the importance of non-disciplinary skills in engineering training and that they play a substantial role in employability. Hence, this study aims to analyze the degree of development of employability skills in students/graduates of five engineering programs at a public higher education institution. A total of 505 people participated in the study, including students in their last semesters and graduates of the last two years. A quantitative research methodology was used, with a cross-sectional non-experimental design and a correlational scope. Data analysis was done with inferential statistics. It was possible to demonstrate that there are significant differences in the training of engineers from the different programs of the same university in terms of employability and this, in turn, depends on three factors such as personal strengths that increase employment potential self-perceived employment opportunities and professional well-being as the realization of employment potential. For this, it is necessary to make Higher Education Institutions (HEIs) point out the need to participate in activities that improve undergraduate education and the curriculum to enhance the employability of engineers.